Business Continuity and Disaster Risk Management in Business Education: Case of York University (2016)
Increasing levels of business disruptions and disaster events on one hand while local, national and international campaigns on the other have increased businesses’ awareness, attention and demand for the need for business continuity management. As more and more businesses are looking to integrate disaster risk and business continuity management into their business operations and decision making processes, the need for such expertise has also increased. Despite these needs, many business schools around the world have not fully identified, realized or addressed them. While there are several models for integrating disaster risk and business continuity management in business education, York University has established undergraduate and graduate level disaster and emergency management programs in a business school setting to address these growing needs. Through this integration, considerable numbers of business students enroll in disaster risk management, and business continuity courses. Knowledge and skills that students acquire through these courses make them informed and knowledgeable players in business continuity management teams in their varied work places.